What’s Harder: Reading, Writing, Listening or Speaking?: Ecuadorian Students’ Perceptions of the Four Macro-Skills - Mohini Tattersall, Rachel (Ecos de la Academia, 2021)
This study sought to better understand the relationship between Ecuadorian university students’ highschool English learning experiences and their emotions regarding the four macro-skills. This built on previousstudies about affect in second language learning. The main study methods employed were surveyswith short answer sections, analysing the trends using t-tests, graphic representation and means, as wellas coding non-empirical responses. The study found a weak relationship between students’ high schoolexperiences and their perceptions for speaking and writing, and a very weak relationship for listening andreading. Findings provide an important contribution to work on EFL in Latin American tertiary contexts,as well as adding to the discussion of affect in second language learning. The study presents a meditationupon the role of emotion in learning that would be valuable for all EFL and second language professional